Characteristics of waiter service in Filipino family type restaurants in Quezon City - Abreu, Michelle G.
Nowadays, hundredsof books have been published about the English, Russian, American and French Style of Service. However, rarely does a reader find a book that extensively and intensively tackles the Filipino style of service. It is for this very reason that this paper has been conceptualized. This paper aims, first and foremost, to characterize or describe the kind of waiter service being offered in selected Filipino Family-type restaurants in Quezon City. Specifically, this paper intends to determine: (1) the differences and/or similarities between the Filipino standard of service and International standards of service (i.e. American, English, Russian and French); (2) the factors involved in shaping the waiter service in Filipino Family-type restaurants; and, if necessary, (3) to give recommendations as to how the waiter service in Filipino Family-type restaurants may be improved. Much of the data found in this research paper were gathered by visiting selected Filipino Family-type restaurants in Quezon City, particularly Bakahan at Manukan, Bangus, Barrio Fiesta, Cabalen, Paseo, Pinausukan and Sangkalan; and interviewing their respective Dining Room Managers, as they are the ones who are deemed to know more about the subject of waiter service. To support the statements of the interviewees, a survey among the customers of the said establishments was also conducted. Finally, to be able to give an objective analyses of the information at hand, quality time at libraries and surfing the information super-highway (internet) looking for any materials related to their topic of waiter service was done.